Cooperative Multifunctional Self‐Propelled Paramagnetic Microrobots with Chemical Handles for Cell Manipulation and Drug Delivery. (6th September 2018) - Villa, Katherine; Krejčová, Ludmila; Novotný, Filip; Heger, Zbynek; Sofer, Zdeněk; Pumera, Martin
Abstract: Autonomous self‐propelled micromachines, taking energy from surrounding environment and converting it to their motion, are on the forefront of the research for smart materials in the recent years. Owing to their self‐propulsion mechanism, they have demonstrated to be more efficient drug carriers than passive particles. Here, multifunctional superparamagnetic/catalytic microrobots (PM/Pt microrobots) for cell manipulation, anticancer drug loading, and delivery to breast cancer cells are presented. These PM/Pt microrobots are fabricated from superparamagnetic polymer particles with iron oxide in their interior and an external tosylated surface, which is half‐covered by a catalytic platinum (Pt) layer. This result in a triple‐functionality—tosyl group‐rich polymer layer can bind molecules and biological materials, Pt layer can catalyze decomposition of hydrogen peroxide, providing propulsion to the microrobots and magnetic part allows for manipulation by magnetic field. PM/Pt microrobots are able to move as individual robots and to "team‐up" under influence of weak magnetic field by forming chains of the micromachines to perform collective actions, such as capture and transportation of cancer cells. The efficacy of PM/Pt microrobots to perform several tasks without complex surface functionalization steps simplifies the applicability of such multifunctional devices toward diverse biomedical applications. Abstract : Multifunctional superparamagnetic/catalytic (PM/Pt) microrobots that can swim autonomously in a chemical fuel and "team up" into chains under the influence of a weak magnetic field to overcome the speed limitations in complex biological media are presented. These PM/Pt microrobots are able to perform multiple tasks, such as cargo loading, cell manipulation, and drug delivery.